Queering Chinese kinship : queer public culture in globalizing China - Song, Lin (Writer on gender studies) (Queer Asia., 2022)
What does it mean to be queer in a Confucian society in which kinship roles, ties, and ideologies are of such great importance? This book makes sense of queer cultures in China - a country with one of the largest queer populations in the world - and offers an alternative to Euro-American blueprints of queer individual identity.